Tumefactive Demyelination Lesions: Report on Three Cases - Chi-Ju Lin; Shih-Chieh Lin; Kai-Wei Yu; Wen-Yu Ou Yang; Yi-Chung Lee; Yi-Chu Liao (Acta Neurologica Taiwanica)
Purpose: Tumefactive demyelination (TD) lesion and its subtype Balo’s concentric sclerosis (BCS), are rare manifestations of central nervous system demyelinating disease. Because of its rarity, physicians might hesitate in reaching a diagnosis or initiating steroid pulse therapy. This study aims at pinpointing the key neuroimaging features to distinguish TD lesions from surgical conditions, and illustrating the clinical outcomes of patients with TD lesions. Case report: Two of the three patients had solitary TD lesions, one 47-year-old man presenting with newly onset seizure and another 54-year-old women suffering from progressive hemiparesis. The male patient underwent craniotomy for mass excision without further steroid therapy, while the female patient received methylprednisolone pulse therapy only. Both patients remained free of clinical and radiological relapses over the past 6-7 years, leading to the diagnosis of clinically isolated syndrome. The third case is a 30-year-old woman with subacute onset of dysarthria and hemiparesis. She had two BCS lesions along with other demyelinating lesions in the juxtacortical and periventricular regions, cerebellar peduncles, and spinal cord, fulfilling dissemination in time and space. Her neurological deficits resolved after pulse therapy, and she received long-term disease modifying therapy for multiple sclerosis. Conclusion: This study underscores the diverse neuroimaging and clinical presentations of patients with TD lesions, and emphasizes the importance of clinical vigilance regarding this rare condition.